Gwathmey Siegel (Massachusetts : Rockport, 1995)
10 viviendas residenciales en distintos países
Keywords: GWATHMEY, CHARLES; SIEGEL, ROBERT; ARQUITECTOS; GWATHMEY-SIEGEL; ARQUITECTURA CONTEMPORANEA; VIVIENDAS